How old is the Babo Balukbuk site? The use of tradeware ceramics and radiocarbon dating in identifying the age of Porac, Pampanga, Philippines - Melendres, Rhayan G. (2014)
access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/4369/3965
Keywords: Archaeological research; Archaeological excavations; Porac (Pampanga)